2008
DOI: 10.5424/sjar/2008064-348
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of raw and extruded chickpeas (Cicer arietinum L.) for growing chickens

Abstract: The effects of the inclusion of different concentrations (0, 100, 200 and 300 g kg -1 ) of raw and extruded chickpeas on performance, digestive organ sizes, and protein and fat digestibilities were studied in one experiment with growing broiler chickens (0 to 21 days of age). Data were analyzed as a 3 x 2 factorial arrangement with three levels of chickpea with or without extrusion. A corn-soybean based diet was used as a positive control. Increasing chickpea content in the diet did not affect weight gain, fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
3
23
0
2
Order By: Relevance
“…Results of chemical composition in Table (2) indicated that, Chickpea screenings by-products had higher CP, EE contents and lower CF, neutral detergent fiber (NDF) and acid detergent fiber (ADF), ADL contents, compared with barley. These results are in agreement with those obtained in the literature (Chavan et al (1989), Brenes et al (2008), Lardy and Anderson (2009) and Bampidis and Christodoulou (2011)). While, Ghezeljeh and Mesgaran (2010) reported that chickpea pre-screening by-products has high CP, EE, CF and low NDF, ADF (279, 78, 72, 351 and 96 g/kg DM, respectively) compared with the present study.…”
Section: Chemical Evaluation Of Chickpea Screenings By-productssupporting
confidence: 94%
See 2 more Smart Citations
“…Results of chemical composition in Table (2) indicated that, Chickpea screenings by-products had higher CP, EE contents and lower CF, neutral detergent fiber (NDF) and acid detergent fiber (ADF), ADL contents, compared with barley. These results are in agreement with those obtained in the literature (Chavan et al (1989), Brenes et al (2008), Lardy and Anderson (2009) and Bampidis and Christodoulou (2011)). While, Ghezeljeh and Mesgaran (2010) reported that chickpea pre-screening by-products has high CP, EE, CF and low NDF, ADF (279, 78, 72, 351 and 96 g/kg DM, respectively) compared with the present study.…”
Section: Chemical Evaluation Of Chickpea Screenings By-productssupporting
confidence: 94%
“…Meantime, insignificant differences were observed among 100% CSB and control group in DM, OM, CP, CF and NFE. These results agreed with those reported by Brenes et al (2008); Nalle (2009) who reported that digestibility and biological value of chickpea nutrients for poultry are high. While, Viveros et al (2001) noticed that the inclusion of 300 g/kg raw Kabuli chickpeas in diets of broiler chickens reduced ileal starch digestibility by 3%, ileal CP digestibility by 18% and apparent ME by 9% compared with those fed the control diet without chickpea.…”
Section: Digestibility and Nutritive Values Of The Experimental Dietssupporting
confidence: 93%
See 1 more Smart Citation
“…Sarica et al (2014) indicated that OEO (250 or 500 ppm) did not influence jejunum relative length in 3-d-old chicks, although the relative length of ileum was higher by 500 ppm OEO at d 14 when compared to control. Brenes et al (2008) indicated that relative weights of pancreas and liver and relative lengths of duodenum, jejunum and ceca increased in response to increasing chickpea seed which contains antinutritional factors such as protease inhibitors and polyphenols. Moreover, Miles et al (2006) reported that dietary inclusion of antibiotic growth promoters reduced intestinal length.…”
Section: Discussionmentioning
confidence: 99%
“…Ekstrüde edilmiş nohut içeren rasyonlar, çiğ nohut içerenlere göre ağırlık kazancını arttırmış, pankreas ağırlığını ise kısmen azaltmıştır. Rasyona 300 g/kg'a kadar nohut ilavesi etlik piliçlerin besi performansı üzerine olumsuz bir etkide bulunmamış, fakat bazı sindirim organlarında ağırlık artışına neden olmuştur (Brenes et al, 2008).…”
Section: Tane Nohutun Kanatlı Beslenmesinde Kullanımı Konusunda Yapılunclassified